Remaking France : Americanization, Public Diplomacy, and the Marshall Plan. - McKenzie, Brian Angus, 1970- (Explorations in culture and international history series., 2007)
Public diplomacy, neglected following the end of the Cold War, is once again a central tool of American foreign policy. This book, examining as it does the Marshall Plan as the form of public diplomacy of the United States in France after World War Two, offers a timely historical case study. Current debates about globalization and a possible revival of the Marshall Plan resemble the debates about Americanization that occurred in France over fifty years ago. Relations between France and the United States are often tense despite their shared history and cultural ties, reflecting the general f.